PENGARUH PROGRAM SPIRITUAL TERHADAP MOTIVASI PEMINDAHAN LATIHAN, KEHIDUPAN BERAGAMA DAN PRESTASI KERJA DI KALANGAN ANGGOTA ANGKATA TENTERA MALAYSIA - Muhammad Syukri Zahari Al-Hafiz (Tesis, 2021)
This study has two objectives. First to analyse the relation between the spritual program on leading religion life and work performance. Second, to analyse about the roles of motivational transfer program as an intervening variable between the influence on spritual program. The result of analysis from model smart PLS produced two findings. First, all three element of spiritual program have significant relatiobnship with the influence of the program. Second, motivational training transfer plays a positive role as an intervening variable in relation to spiritual program and its influence.